A Case Report of Dextrocardia with Hypertensive Emergency and Congestive Heart Failure: A Rare Condition - Ramadhani, Fikar; Zahra, Nabila Luthfiyyah (The International Journal of Medical Science and Health Research, 2024)
Introduction : Dextrocardia is a rare congenital anomaly affecting the heart. The range of cardiac problems linked to dextrocardia is extensive. This case report seeks to enhance the current knowledge by providing a clinical description of dextrocardia accompanied by hypertensive emergency and congestive heart failure. Case Presentation : A 39-year-old woman came to the Emergency Department of RSI Sultan Hadirin Jepara, having vomitted more than ten times since last night. Vomiting was preceded by nausea. The patient has been experiencing shortness of breath for three years, particularly when sleeping with only one pillow, necessitating the use of multiple pillows. Through additional physical and supporting examinations, the patient was diagnosed with dextrocardia with hypertensive emergency and congestive heart failure. Conclusion : Dextrocardia is a rare birth defect characterized by a variety of complicated structural abnormalities in the heart. There is no difference in symptoms and signs in patients with congestive heart failure in dextrocardia or levocardia. So that the approach to managing congestive heart failure in our patient is identical. Gaining a comprehensive understanding of this uncommon ailment is essential for delivering suitable medical treatment and effectively managing any problems in affected persons.